2021
DOI: 10.1111/jbi.14210
|View full text |Cite
|
Sign up to set email alerts
|

Widespread misperception about a major East Asian biogeographic boundary exposed through bibliographic survey and biogeographic meta‐analysis

Abstract: Aim:The Watase line, a major biogeographic boundary between Palearctic and Oriental realms in East Asia, is generally drawn between Akuseki and Kodakara Islands of the Northern Ryukyu archipelago, Japan. However, no evidence can be found to support the positioning of the boundary between these two tiny volcanic islands. This study aimed to confirm whether and where the biogeographical boundary should be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Herein, the biogeographical border of the Watase line, which has been described to exist between Kodakara Island and Akuseki Island (Yakushima Island and Amami Island in this study; Figure S1). Komaki (2021) indicated that the position of the border is ambiguous and proposed the question of whether a clear line exists. Since our primary objective was to investigate the impact of historical factors on land connections rather than to define a clear border, we opted to assume a boundary between Yakushima and the Amami Islands (Figure S1).…”
Section: Study Areamentioning
confidence: 99%
“…Herein, the biogeographical border of the Watase line, which has been described to exist between Kodakara Island and Akuseki Island (Yakushima Island and Amami Island in this study; Figure S1). Komaki (2021) indicated that the position of the border is ambiguous and proposed the question of whether a clear line exists. Since our primary objective was to investigate the impact of historical factors on land connections rather than to define a clear border, we opted to assume a boundary between Yakushima and the Amami Islands (Figure S1).…”
Section: Study Areamentioning
confidence: 99%
“…Adherence to this polarized argument (e.g., Heads, 2005) may hinder progress toward considering and understanding the importance of many other factors (De Queiroz, 2014) such as long‐distance dispersal (Welt & Raxworthy, 2022) and the role of ecological adaptation (Zhou et al., 2020), which often contribute to unique floral and faunal assemblages of celebrated island communities (Gillespie, 2002; Lomolino et al., 2017; Wagner & Funk, 1995; Wallace, 1869). In East Asia, the Ryukyu Island Chain had been studied extensively, as a fertile region to test the relative influence and impact of geohistorical events, deep‐sea barriers, and sea currents in shaping this archipelago's highly endemic, insular biota (Kawamura et al., 2016; Komaki, 2021; Yang et al., 2018). However, ecological factors such as host‐specificity, adaptation to local environments, and interspecific competition have been rarely considered (but see Sato et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Combined with knowledge of phylogeny and ecological traits, the distribution data could contribute to identification of biodiversity hotspots and assessment of conservation prioritisation ( Loiseau et al 2020 , Jetz et al 2014 , Benedetti et al 2022 ). Macroecology and biogeography also require large-scale distribution data to explain spatial patterns of diversity ( Davies et al 2007 , Lennon et al 2001 , Komaki 2021 ). The impact of global climate change on birds has caused widespread discussion and much of this evidence is based on the knowledge of range shifts ( Gillings et al 2015 , Hitch and Leberg 2007 , Huntley et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%